Women in Small and Medium Sized Family Firms: Theory and Practice - D'Allura, Giorgia Maria; Bannò, Mariasole; Dawson, Alexandra; Torchia, Mariateresa; Cesaroni, Francesca Maria (Piccola Impresa / Small Business, 2022)
Research on women presence in family firms has increased in the last decades. Nevertheless, most of the current understanding has been developed by studying large firms, leaving the unique and distinctive challenges of women involvement in small family firms still underexplore. This editorial offer an interpretative lens of the articles in this special issue through the microfoundation approach and Antecedents, Decisions and Outcomes (ADO) framework. Second, it summarizes the studies included and, finally, suggests directions for future research. Women are still not a valued asset. Consistent with the goals that inspired this special issue, the findings have important practical implications, as they provide valuable indications and suggestions for firms to be more inclusive towards women.